2010
DOI: 10.1016/j.nut.2009.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Soybean diet alters the insulin-signaling pathway in the liver of rats recovering from early-life malnutrition

Abstract: Adult rats maintained with a soybean diet exhibited insulin resistance due, at least in part, to alterations in the early steps of the insulin signal transduction pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…In this study, rats recovered with the soybean diet showed low body weight and normalization of serum triacylglycerol concentrations, corroborating the well-known favorable effect of soy protein containing various levels of isoflavones on somatic parameters [ 39 , 40 ] and serum triacylglycerol levels [ 41 , 42 ]. However, contrary to the observations that soy protein reduces serum insulin levels [ 42 , 43 ], we verify here, as in previous studies [ 23 , 24 , 26 ], that the consumption of a soybean flour diet increased serum insulin concentrations. This effect may be attributable to genistein, which increases insulin secretion due to its ability to activate the cAMP-PKA pathway [ 26 ].…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…In this study, rats recovered with the soybean diet showed low body weight and normalization of serum triacylglycerol concentrations, corroborating the well-known favorable effect of soy protein containing various levels of isoflavones on somatic parameters [ 39 , 40 ] and serum triacylglycerol levels [ 41 , 42 ]. However, contrary to the observations that soy protein reduces serum insulin levels [ 42 , 43 ], we verify here, as in previous studies [ 23 , 24 , 26 ], that the consumption of a soybean flour diet increased serum insulin concentrations. This effect may be attributable to genistein, which increases insulin secretion due to its ability to activate the cAMP-PKA pathway [ 26 ].…”
Section: Discussioncontrasting
confidence: 87%
“…Thus, in this and in a previous study [ 37 ], the interplay between liver insulin resistance, which induces SREBP-1c overexpression, and other factors (e.g., genistein and soy protein) that suppress its expression resulted in no change in nSREBP-1c contents or SREBP-1c mRNA expression. An adequate explanation for the paradoxical association of liver insulin resistance with unmodified nSREBP-1c concentrations is the mild hyperinsulinemia and the euglycemia observed in our animals fed with soybean, as noted here and previously [ 24 ]. SREBP-1c expression has been shown to be stimulated by glucose and insulin and repressed by glucagon [ 9 , 10 , 48 ].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Most animal studies have shown an improvement in insulin sensitivity and other parameters of glucose homeostasis [22,31,32,33,34]. However, one recently published study showed that in rats recovering from early life malnutrition that were fed on a soybean diet, there was an alteration in the insulin signaling pathway, leading to an increase in insulin resistance [35]. In humans, early studies done in diabetics registered an improvement in glycemic control [36], but recently published studies have not shown any beneficial effects on indices of glucose homeostasis [21,37].…”
Section: Resultsmentioning
confidence: 99%